DESCRIPTION HISTORICAL AND PSYCHOLOGICAL PROCESS IN THE CONTEXT OF «OPEN PSYCHOLOGICAL CRISIS» IN THE VIEWS OF S. RUBINSTEIN - Larin, Dmitro (PSYCHOLOGICAL JOURNAL, 2017)
This article characteristic historians psychological process in the context of the period of «open psychological crisis» according to the conceptual approach of the outstanding scientist, Sergey Leonidovich Rubinstein. Described methodological principles and their significance for historical and psychological sciences, outlined the problems of psychological schools first third of the XX century. Special attention is drawn to the formation of behavioral psychology - behaviorism and reflexology. All the problems of theory and history of psychology S. L. Rubinstein focused on a single principle by which solved the central problem of psychology − the problem of man. On the need to review the psychological tenets and demands testified practices that could not be ignored by scientists. Orientation to practice expressed not only in the philosophy of pragmatism, especially popular in the US but also in the development of interdisciplinary issues, especially along with medicine and pedagogy. If clinical data is heavily influenced by the French psychology (as mentioned above) and on the formation of depth psychology, the task of studying and education of the «new man» , the development of new approaches to socialization were leading in the United States and Russia, affecting the development of behaviorism and Soviet psychology. Our historical and psychological studies are based on the principles of objectivity on methodological research, multi-dimensional and multi-existence of the subject, the study of phenomena in the history of psychology of development, unity and historical logic, knowledge in the form of a spiral, fighting materialism and idealism. The development of psychological science is largely determined by how correctly and comprehensively and deeply researched its theoretical foundations. Any backlog of science in this respect is the need for its lag in the deployment of specific research, reducing its level of scientific and practical value.